The promise of heaven : 31 reasons to get excited about your eternal home - Jeremiah, David, 1941- (W Publishing Group, an imprint of Thomas Nelson, 2025)
"Have you ever looked around and thought, There has to be more than this? You're not alone . . . and you're right. Heaven is your forever home. In The Promise of Heaven, Dr. David Jeremiah invites you to lift your eyes above the disappointments and burdens of this world and catch a glimpse of the one to come. In 31 short, hope-filled chapters, you'll explore what the Bible really says about heaven. With biblical truth and powerful real-life stories, this book will stir your longing for eternity and give you strength for whatever you're facing today. Because when your heart is set on heaven, life starts to look different. Worry loses its grip. Pain doesn't feel so final. Joy starts to return, even in the middle of hard days. And you begin to live with quiet confidence, knowing that something far better is ahead." --